(untitled) (Baghdad Science Journal, 2023)
In this research, carbon nanotubes (CNTs) is prepared through the Hummers method with a slight change in some of the work steps, thus, a new method has been created for preparing carbon nanotubes which is similar to the original Hummers method that is used to prepare graphene oxide. Then, the suspension carbon nanotubes is transferred to a simple electrode position platform consisting of two electrodes and the cell body for the coating and reduction of the carbon nanotubes on ITO glass which represents the cathode electrode while platinum represents the anode electrode. The deposited layer of carbon nanotubes is examined through the scanning electron microscope technique (SEM), and the images throughout the research show the formation of carbon nanotubes. In the second part of the research, a dye-sensitized solar cell (DSSC) is prepared to utilize carbon nanotube as the cathode electrode, titanium oxide nanoparticles as the anode electrode by using a natural dye (pomegranate dye). The assembled dye-sensitized solar cell (DSSC) is tested by two electrodes potentiostat using Xenon light source and all parameters are established; Vocp, Imax, Vmax, Isc and calculated full factor and conversion efficiency.